(untitled) (Conferencea, 2024)
COVID-19 is a serious infectious disease with a high mortality rate. According to data provided by the WHO, the current coronavirus statistics as of 2024 (worldwide) show that it has spread to 229 countries, the total number of infections is 704,753,890, and the number of deaths is 7,010,681 (1.0%).